‘I’ve lived and bred violence my whole life’: understanding violence in the Irish Prison Service through the lens of the power threat meaning framework - Gallagher, Orla (Psychology, crime & law, 2025)
In 2018 the Irish Prison Service (IPS) opened the National Violence Reduction Unit (NVRU), which became home to a small amount of prisoners managed under the Violently Disruptive Prisoner (VDP) policy, who were repeatedly engaged in very serious violence in prison. The NVRU shifted practice under the VDP policy to a joint operational-psychological approach, with the aim of understanding the violent behaviour of these prisoners and working with them to reduce it. This study explored NVRU prisoners’ understandings of the origins, experiences and expressions of their violent behaviour through the lens of the Power Threat Meaning Framework (PTMF). Despite difficulties engaging this cohort, half (n = 3) of all prisoners residing in the NVRU during its first year participated in semi-structured interviews. Participants identified six themes: (1) power, (2) threat, (3) meaning, (4) threat response, (5) function of threat response and (6) moderating factors. In doing so they identified many a priori elements of the existing provisional PTMF, whilst also contributing novel elements related to their specific and subjective personal experiences. These findings are interpreted in the context of existing empirical research. Implications for future research, and policy and practice within and beyond the NVRU, are suggested.